Caracterização e estimativa da diversidade genética de acessos de Urochloa - Martins, Carla Tatiana de Vasconcelos Dias (2024)
The grass of the genus Urochloa is a forage grass of African origin and is among the most used species in pastures, presenting great importance for agriculture. However, the extensive use of these forages has required genotypes increasingly productive, resistant to pests, diseases, and water deficit. This study aims to generate and organize information on accesses of the genus Urochloa through morphoagronomic, cytogenetic, and molecular characterization, indicating genotypes with future potential for use in species breeding programs. For morphoagronomic characterization, 15 Urochloa spp. accesses were used based on 24 quantitative and qualitative descriptors of Brachiaria. The obtained data were subjected to analysis of variance, Scott-Knott means grouping test, and for divergence determination, both quantitative and qualitative descriptors were analyzed by the UPGMA hierarchical method, from which a dendrogram was generated. For cytogenetic characterization, 13 accesses were used, using root tip material treated with 2 mM 8-hydroxyquinoline, fixed in Carnoy's solution. The roots were subjected to enzymatic digestion with 2% cellulase and 20% pectinase, and the chromosome staining technique with CMA/DAPI fluorochromes was used to locate heterochromatic regions. For molecular characterization, 21 SSR microsatellite markers were used, where the amplified fragments were coded for dominant homozygote (1.1), heterozygote (1.2) e recessive homozygote (2.2) to estimate the genetic relationships between Urochloa accesses using Genes software. As a result of morphoagronomic characterization, the accesses showed great variability for most of the evaluated descriptors. The UmCO-2 (2), UmCO-13 (2), UmCO-5 (2), and UmCO-8 (1) accesses stood out for presenting promising characteristics for forage production, while the UmCO-11 (2) and UmCO-2 (2) accesses showed greater genetic divergence. In cytogenetic characterization, accesses with 2n=14 were identified for the species U. mosambicensis, U. oligotricha, U. advena, and U. brachyura, and 2n=28 for U. mosambicensis and Urochloa sp. The analysis with double staining CMA/DAPI allowed the visualization of two to seven bands in diploid accesses, while in tetraploid accesses, this number varied from three to six bands. Regarding the results of PCR amplifications, it was possible to identify the presence of polymorphic bands in the markers, allowing the separation of the accesses into six groups. The results of this study suggest that there is great variability among the studied accesses, which allows their use in selection and breeding programs